Fine-Scale Population Genetic Structure and Parapatric Cryptic Species of Kuruma Shrimp (Marsupenaeus japonicus), Along the Northwestern Pacific Coast of China - Wang, Panpan; Chen, Baohua; Zheng, Jinbin; Cheng, Wenzhi; Zhang, Heqian; Wang, Jun; Su, Yongquan; Xu, Peng; Mao, Yong (Frontiers in Genetics, 2020)
The kuruma shrimp (Marsupenaeus japonicus) includes two cryptic species, which are distributed mostly allopatrically but co-occur in the northern South China Sea (from Huilai to Beihai). To obtain a better understanding of the fine-scale genetic structure and parapatric diversification of these two varieties in the northwestern Pacific region, we used a genotyping-by-sequencing (GBS) and comparative transcriptomics approach to establish their phylogenetic relationships. Using the GBS technique, we genotyped 28891 SNPs in 160 individuals in the Northwest Pacific. The results supported two highly diverged evolutionary lineages of kuruma shrimp (var. I and II). The ND and XM populations showed complex genetic patterns, which might be affected by the complex environment of the Taiwan Strait. In addition, the migration rates and inbreeding coefficients of XM and BH were much lower than those of the other populations, which might be related to the land-sea changes and complex ocean currents in the Taiwan Strait and Qiongzhou Strait. Based on the synonymous substitution rates (ds) of 2491 candidate orthologs, we estimated that the divergence time between the two varieties was 0.26~0.69 Mya. Choice and no-choice interbreeding experiments provided support for the biological species concept, by showing the existence of reproductive isolation or incompatibility. In view of these differences between the two Marsupenaeus species, we believe that it is essential and urgent to establish a genetic database for each and reevaluate their ecological suitable conditions in order to improve species-specific culturing techniques. Moreover, this research can serve as a case study for future research on speciation and hybridization.